Chronic Calcific Pancreatitis, Type IIIc Diabetes Mellitus: A Case Report from Chennai, India - K, Kirthikaraju; Saravanakumar, Keshavini; Muppa, Leena (Indian Journal of Pharmacy Practice)
Diabetes Mellitus (DM) encompasses a spectrum of metabolic disorders, with type 3c DM, also known as pancreatogenic diabetes mellitus, arising secondary to pancreatic disease. Despite its prevalence, type 3c DM remains significantly underdiagnosed due to overlapping symptoms with type I and type II DM, complicating the differentiation process. This case report features a 53-year-old male patient who came with complaints of epigastric pain for the past 2 days. The patient is a known case of chronic pancreatitis, had elevated blood glucose, lipase, and liver enzyme level, and had a weight loss of about 15 kg in the last 10 years. CT Abdomen suggested chronic calcific pancreatitis with multiple intraductal calculi and mild central intrahepatic biliary radicle dilatation with mildly dilated common bile duct. From the above-mentioned evidence, the patient was diagnosed with Type 3c diabetes mellitus, which was initially misdiagnosed as Type 2 DM, benign biliary stricture of Common Bile Duct (CBD) and chronic calcific pancreatitis. The patient was treated with insulin and metformin for the hyperglycemic state. For chronic pancreatitis, ERCP was done and a stent was placed. Standardizing diagnostic criteria and increasing awareness among healthcare providers are essential steps toward improving the diagnosis and management of this often overlooked form of diabetes mellitus.
Keywords: Type 3c diabetes; Diabetes mellitus; Chronic pancreatitis; Pancreatogenic diabetes mellitus; Exocrine pancreatic insufficiency